FDI versus exports. Substitutes or complements? A three nation model and empirical evidence - Harald Oberhofer; Michael Pfaffermayr (University of Innsbruck, Department of Public Finance, 2007)
There are two main options for companies to serve foreign markets: exports and foreign direct investment (FDI). Based on the Helpman, Melitz and Yeaple (2004) model for two host countries this paper derives a clear theoretical prediction for the decision between both strategies. A bivariate probit model is estimated using AMADEUS database to analyse the probability of using one or the other strategy. The empirical evidence indicates that a considerable number of companies use a combination of both strategies to serve foreign markets, which is in line with the analyzed three country model.
Keywords: C35; D21; F12; 330; exports; foreing direct investment; three nations model; bivariate probit estimation; Internationale Markteintrittsstrategie; Export; Direktinvestition; Mehr-Länder-Modell; Probit-Modell; Schätzung; Europa